A peptide-derived strategy for specifically targeting the mitochondria and ER of cancer cells: a new approach in fighting cancer. Issue 23 (26th May 2022) - Sohn, Yang Sung; losub-Amir, Anat; Cardenas, Alfredo E.; Karmi, Ola; Yahana, Merav Darash; Gruman, Tal; Rowland, Linda; Marjault, Henri-Baptiste; Webb, Lauren J.; Mittler, Ron; Elber, Ron; Friedler, Assaf; et al.
Abstract : An effective anti-cancer therapy should exclusively target cancer cells and trigger in them a broad spectrum of cell death pathways that will prevent avoidance. Abstract : An effective anti-cancer therapy should exclusively target cancer cells and trigger in them a broad spectrum of cell death pathways that will prevent avoidance. Here, we present a new approach in cancer therapy that specifically targets the mitochondria and ER of cancer cells. We developed a peptide derived from the flexible and transmembrane domains of the human protein NAF-1/CISD2. This peptide (NAF-1 44-67 ) specifically permeates through the plasma membranes of human epithelial breast cancer cells, abolishes their mitochondria and ER, and triggers cell death with characteristics of apoptosis, ferroptosis and necroptosis. In vivo analysis revealed that the peptide significantly decreases tumor growth in mice carrying xenograft human tumors. Computational simulations of cancer vs. normal cell membranes reveal that the specificity of the peptide to cancer cells is due to its selective recognition of their membrane composition. NAF-1 44-67 represents a promising anti-cancer lead compound that acts via a unique mechanism.